Influence of emulsion composition and spray-drying conditions on microencapsulation of tilapia oil - Huang, Hui (Springer India, 2012)
The influence of processing conditions on the microencapsulation of tilapia oil by spray drying was studied. Trehalose, gelatin, sucrose and xanthan were used as emulsion composition. The experimental parameters of spray drying such as inlet air temperature, solid content, drying air flow rate and atomizing pressure were optimized using a central composite design. Encapsulation efficiency and lipid oxidation were determined. Bulk density, powder morphology and particle size were also analyzed. Trehalose improved the glass transition temperature of wall material significantly and prevented the oxidation of the fish oil. Encapsulation efficiency reached a maximum of 90 % under optimum conditions with an inlet air temperature of 121 °C, a drying air flow rate of 0.65 m(3)/min and a spray pressure of 100 kPa.